2005
DOI: 10.1051/ebr:2005014
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for the exposure of ground beetles to Cry1Ab from transgenic corn

Abstract: Non-target organisms associated with the soil might be adversely affected by exposure to the Cry1Ab protein from Bacillus thuringiensis (Bt) in transgenic corn (Zea mays L.). To check for such exposure, we used ELISA to test for Cry1Ab in ground beetles collected live from fields with Bt corn residues and Bt corn (Bt/Bt), Bt corn residues and non-Bt crops (Bt/non-Bt), or non-Bt corn residues and non-Bt crops (non-Bt/non-Bt). In fields with Bt corn residues (Bt/Bt and Bt/non-Bt), Cry1Ab was present in all seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 14 publications
1
40
2
Order By: Relevance
“…In some cases, such as spider mites, herbivores concentrate the toxins at levels significantly exceeding the titers present in plants (Dutton et al, 2002;Obrist et al, 2006a). Numerous studies have documented the transfer of toxins from plants to various predatory taxa (Harwood et al, 2005;Zwahlen and Andow, 2005;Obrist et al, 2006a). Retention of the toxin in the natural enemies appears to be relatively short-lived, but the relative abundance and season-long persistence of intoxicated prey make repeated exposure likely for many natural enemies in GM crops.…”
Section: Toxin-containing Prey On Gm Cropsmentioning
confidence: 99%
“…In some cases, such as spider mites, herbivores concentrate the toxins at levels significantly exceeding the titers present in plants (Dutton et al, 2002;Obrist et al, 2006a). Numerous studies have documented the transfer of toxins from plants to various predatory taxa (Harwood et al, 2005;Zwahlen and Andow, 2005;Obrist et al, 2006a). Retention of the toxin in the natural enemies appears to be relatively short-lived, but the relative abundance and season-long persistence of intoxicated prey make repeated exposure likely for many natural enemies in GM crops.…”
Section: Toxin-containing Prey On Gm Cropsmentioning
confidence: 99%
“…Predators can encounter transgene products like plantexpressed Bt toxins when feeding on plant material, for example, pollen, nectar, or leaf exudates, and, additionally, when preying on other organisms that have consumed transgenic plant tissue or toxin-loaded prey (Harwood et al 2005;Zwahlen and Andow 2005). Further, prey organisms that have ingested transgene products might not only pass the unchanged transgene product from the plant to the predator but also modify it by their own metabolism, potentially altering their biochemical activity and becoming more or less harmful to predators (Andow and Hilbeck 2004).…”
mentioning
confidence: 99%
“…Numerous potential prey species for spiders tested positive for Bt-endotoxins from the field, including several beetles (Coleoptera), true bugs (Hemiptera), moth larvae (Lepidoptera: Noctuidae), adult and nymphal crickets (Orthoptera: Gryllidae), harvestmen (Opiliones), millipedes (Diplopoda: Julida), centipedes (Chilopoda: Lithobiomorpha, Geophilomorpha), and earthworms (Haplotaxida: Lumbricidae) (Table S2). Previous studies have also shown clear evidence for the uptake of Cry1Ab Bt-endotoxins from transgenic corn by potential prey items, including corn flea beetle Chaetocnema pulicaria (Coleoptera: Chrysomelidae), Japanese beetle Popillia japonica (Newman) (Coleoptera: Scarabaeidae), pink spotted lady beetle Coleomegilla maculata (DeGeer) (Coleoptera: Coccinellidae), and damsel bug Nabis roseipennis Reuter (Hemiptera: Nabidae) (Harwood et al, 2005(Harwood et al, , 2007Obrist et al, 2006;Wei et al, 2008;Zwahlen & Andow, 2005). These studies, as well as our own, found a large degree of variation in the uptake of Cry proteins by different prey species (see Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Techniques using monoclonal and/or polyclonal antibodies, such as enzyme-linked immunosorbent assay (ELISA), have been successfully employed to detect the presence of Bt-endotoxins in field-collected arthropods, such as Coleoptera (Harwood et al 2005(Harwood et al , 2007Peterson et al 2009;Zwahlen & Andow 2005), Acari (Obrist et al 2006;Torres & Ruberson 2008), and Araneae (Harwood et al 2005). Ahmad et al (2005) measured ground-dwelling arthropod abundance (including spiders) and, in parallel, used ELISA to quantify Bt-endotoxin concentration in the soil, but did not test for the uptake of proteins by the arthropods themselves.…”
Section: Introductionmentioning
confidence: 99%